2019
DOI: 10.1093/gbe/evy273
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Patterns of Rapid Molecular Evolution within thep53Network across Mammal and Sauropsid Lineages

Abstract: Cancer is a threat to multicellular organisms, yet the molecular evolution of pathways that prevent the accumulation of genetic damage has been largely unexplored. The p53 network regulates how cells respond to DNA-damaging stressors. We know little about p53 network molecular evolution as a whole. In this study, we performed comparative genetic analyses of the p53 network to quantify the number of genes within the network that are rapidly ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 106 publications
0
7
0
Order By: Relevance
“…This is in contrast to the purifying selection on p53 across mammals (Gaur et al, 2017;Passow et al, 2019), with the exception of the branch leading to elephants (Passow et al, 2019). We also found that species with longer lifespans experienced less variation in selection across the p53 network, whereas those with shorter lifespans were equally likely to have both positive and purifying selection (Passow et al, 2019). A recent publication on Galapagos tortoise genomes (Quesada et al, 2019) identified variants in p53 that are associated with hypoxia tolerance in other species (Zhao et al, 2013), providing an interesting link between this network and stress resistance in an exceptionally long-live species.…”
Section: Molecular Network For Cellular Senescence: P53/p16mentioning
confidence: 84%
See 2 more Smart Citations
“…This is in contrast to the purifying selection on p53 across mammals (Gaur et al, 2017;Passow et al, 2019), with the exception of the branch leading to elephants (Passow et al, 2019). We also found that species with longer lifespans experienced less variation in selection across the p53 network, whereas those with shorter lifespans were equally likely to have both positive and purifying selection (Passow et al, 2019). A recent publication on Galapagos tortoise genomes (Quesada et al, 2019) identified variants in p53 that are associated with hypoxia tolerance in other species (Zhao et al, 2013), providing an interesting link between this network and stress resistance in an exceptionally long-live species.…”
Section: Molecular Network For Cellular Senescence: P53/p16mentioning
confidence: 84%
“…death, senesce, repair), balancing anticancer and anti-ageing mechanisms. Recent work on the comparative genomics of the p53 molecular network provided evidence of positive selection on genes within p53 networks of reptile (both ecto-and endothermic) relative to mammals, with reptiles having more positive selection on upstream genes (p53 and its regulators), especially in lizards and snakes (Passow et al, 2019). This is in contrast to the purifying selection on p53 across mammals (Gaur et al, 2017;Passow et al, 2019), with the exception of the branch leading to elephants (Passow et al, 2019).…”
Section: Molecular Network For Cellular Senescence: P53/p16mentioning
confidence: 99%
See 1 more Smart Citation
“…This observation may provide evidence for the convergent evolution of p53 proteins in organisms with extreme longevity. According to Passow and colleagues, taxa with evidence of positive selection in the TP53 gene are those with the lowest incidences of cancer reported in amniotes (elephants, snakes, lizards, crocodiles, and turtles) [55].…”
Section: Resultsmentioning
confidence: 99%
“…This may be considered as a supportive evidence for the convergent evolution of p53 proteins in organisms with extreme longevity. According to Passow and colleagues, taxa with evidence of positive selection in the TP53 gene are those with the lowest incidences of cancer reported in amniotes (elephants, snakes and lizards, crocodiles and turtles) (Passow et al, 2019). Figure 15: Mutual information to infer convergent evolution of p53 core domains.…”
Section: Figurementioning
confidence: 99%